MODEL PENGEMBANGAN PEMBIAYAAN: SOLUSI STRATEGIS PENGUATAN MODAL USAHA KECIL AGRIBISNIS DI SUMATERA SELATAN - M. Syahirman Yusi (University of Merdeka Malang, 2012)
The objective of this study was to obtain the empirical evidence about the effect of financial development modeltoward the agribusiness small scale enterprises in South Sumatera. Primary data was collected through surveytechnique from 142 samples. Respondents were taken by using random sampling method and was analysed byusing multiple regression. Statistical analysis showed that all of variables which consisted of business climate,banks credit, entrepreneurship, the micro financial institutions, partnership, and multifinance credit had apositive influence. It meant that the hypothesis was not rejected. Among those variables, business climate wasthe most dominant factor. It meant that in strengthening the small scale enterprises capital, the role of governmentwhich created the condusive business climate became the most important factor, but in partial the entrepreneurshipvariable did not have significant effect. It meant the hypothesis was rejected.